Nitrogen losses in ruminant manure management and use of cattle manure vermicast to improve forage quality - Aminu Nasiru; Mahamad Hakimi Ibrahim; Norli Ismail (International Journal of Recycling of Organic Waste in Agriculture)
Ruminants have low efficiency of nitrogen utilisation; unutilised nitrogen is being excreted in the faeces and urine. The most effective way to minimise nitrogen losses in ruminant production is through efficient feeding strategy. Ruminant manure is an inevitable consequence of its production. All these have adverse environmental effects. Composting and vermicomposting have been suggested as efficient tools for recycling manure, these bring a stabilised and sanitised end product for agriculture. Composting process is an accelerated aerobic degradation of fresh organic matter by microorganism to mature compost. Nevertheless, it may bring some environmental problems by releasing gases which include ammonia, methane and nitrous oxide, reduce the agronomic value of the manure and increase the cost of composting through turning of the compost to ensure aeration. To overcome the cost of composting and produce high quality products, vermicomposting is being recommended. Vermicomposting involves the bio-oxidation and stabilisation of organic material by the joint action of earthworm and microorganism. Moreover, the combination of composting and vermicomposting has been considered as a way of achieving stabilised substrates. Ensiled cattle manure treated with straws has been used to improve nutritional quality of ruminant feed and the result was encouraging. Vermicast, an end product of vermicomposting has higher nutrients content compared with manure or composted manure. Therefore vermicomposting of ruminant manure with rice/wheat straws might have the potential of being used as feed supplement to small ruminant. The likely benefit will be an increase in feed intake, increase in microbial protein supply, increase in fibre digestibility and possibly an increase in weight gain. The aim of this review is to discuss nitrogen losses in ruminant production and manure management and to provide an insight on the possibility of using vermicast as feed supplement to ruminants and as probiotic for treating fibrous feed.